Leiomyomatosis Peritonealis Disseminata: MRI Features Before and After Treatment with GnRH Agonist - ACAR, MURAT; Tatli, Servet; Silverman, Stuart G. (My University, 2013)
Leiomyomatosis peritonealis disseminata (LPD) is a rare disorder characterized by multiple subperitoneal benign smooth muscle nodules. It is usually incidentally discovered during cesarean section or laparoscopy. In this paper, we present pre-and-post GnRH treatment MRI findings of a symptomatic patient with LPD.